2014
DOI: 10.1186/1471-2164-15-55
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling to identify genes involved in Fusarium mycotoxin Deoxynivalenol and Zearalenone tolerance in the mycoparasitic fungus Clonostachys rosea

Abstract: BackgroundClonostachys rosea strain IK726 is a mycoparasitic fungus capable of controlling mycotoxin-producing Fusarium species, including F. graminearum and F. culmorum, known to produce Zearalenone (ZEA) and Deoxynivalenol (DON). DON is a type B trichothecene known to interfere with protein synthesis in eukaryotes. ZEA is a estrogenic-mimicing mycotoxin that exhibits antifungal growth. C. rosea produces the enzyme zearalenone hydrolase (ZHD101), which degrades ZEA. However, the molecular basis of resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 49 publications
2
33
0
5
Order By: Relevance
“…(Kosawang et al 2014). Its nuclear genome and transcriptome analyses have been reported (Kosawang et al 2014;Karlsson et al 2015). The fungus is economically important and widely distributed in tropical and temperate zones.…”
mentioning
confidence: 99%
“…(Kosawang et al 2014). Its nuclear genome and transcriptome analyses have been reported (Kosawang et al 2014;Karlsson et al 2015). The fungus is economically important and widely distributed in tropical and temperate zones.…”
mentioning
confidence: 99%
“…Another transcript induced by 2p-ITC codes for the regulatory protein CHK1, which is also involved in responses to DNA damage and cell survival [42]. In Clonostachys rosea, the CHK1 protein was induced in response to oxidative stress by toxins [43]. Because 2p-ITC is a compound causing oxidative stress, it is feasible that CHK1 was induced in A. alternata after the 2p-ITC treatment.…”
Section: Contig Accession Number (Tsa)mentioning
confidence: 98%
“…Therefore, it should be emphasized that even natural compounds could induce tolerance/resistance mechanisms in organisms in the same manner as synthetic chemical products if they were not used properly. In a study with fungal toxins Kosawang et al [43] using a SSH experimental approach reported 443 and 446 differentially expressed clones induced in Clonostachys rosea by deoxynivalenol (DON) and zearalenone (ZEA) toxins, respectively. DON induced proteins involved in the stress response as well as metabolic enzymes (cytochromes c oxidase and P450) while ZEA induced the detoxifying enzyme HD101 and ABC pleiotropic drug transporters.…”
Section: Contig Accession Number (Tsa)mentioning
confidence: 99%
“…According to Kosawang et al (2014), Zearalenone (ZEA) is an estrogenic-mimicing mycotoxin that exhibits antifungal growth. It is a common contaminant in cereal products particularly grains that are frequently infested by Fusarium spp (Brodehl et al, 2014).…”
Section: Introductionmentioning
confidence: 99%